Is the relationship between subjective age, depressive symptoms and activities of daily living bidirectional?. (October 2018) - Rippon, Isla; Steptoe, Andrew
Abstract: Objectives: The aim of the current study was to investigate the prospective association between subjective age and depressive symptoms and activities of daily living (ADLs), and to test for reciprocal relationships. Methods: We used data from 9886 respondents aged 50 years and over who participated in the English Longitudinal Study of Ageing (ELSA). We fitted a series of multiple regression models to analyse the relationships between subjective age, depressive symptoms, and ADL limitations over a four-year period. Results: Following adjustment for demographic, social, cognitive, lifestyle, and health factors, we found that having an older subjective age independently predicted increased ADL limitations ( B = −0.16, 95% CI -0.25, −0.07) and greater depressive symptoms ( B = −0.40, 95% CI -0.57, −0.23). By contrast, we observed no significant associations between depressive symptoms and ADL limitations and future subjective age in the fully-adjusted model. Conclusion: In conclusion, older subjective age is associated with future depression and functional health, but the reverse pattern is confounded by initial health and social factors. These findings indicate that an individual's age identity may have an important effect on both depressive symptoms and activities of daily living. Highlights: Subjective age predicted future depressive symptoms, but not vice-versa. Older subjective age was associated with greater ADL limitations four years later. Subjective age may contribute to future emotional and physical status. There was no convincing evidence that associations were bidirectional.